Visualizing plating-induced cracking in lithium-anode solid-electrolyte cells - Ning, Z; Spencer Jolly, D; Li, G; De Meyere, R; Pu, SD; Chen, Y; Kasemchainan, J; Ihli, J; Gong, C; Liu, B; Melvin, DLR; Bonnin, A; et al. (Springer Nature, 2021)
Lithium dendrite (filament) propagation through ceramic electrolytes, leading to short circuits at high rates of charge, is one of the greatest barriers to realizing high-energy-density all-solid-state lithium-anode batteries. Utilizing in situ X-ray computed tomography coupled with spatially mapped X-ray diffraction, the propagation of cracks and the propagation of lithium dendrites through the solid electrolyte have been tracked in a Li/Li6PS5Cl/Li cell as a function of the charge passed. On plating, cracking initiates with spallation, conical ‘pothole’-like cracks that form in the ceramic electrolyte near the surface with the plated electrode. The spallations form predominantly at the lithium electrode edges where local fields are high. Transverse cracks then propagate from the spallations across the electrolyte from the plated to the stripped electrode. Lithium ingress drives the propagation of the spallation and transverse cracks by widening the crack from the rear; that is, the crack front propagates ahead of the Li. As a result, cracks traverse the entire electrolyte before the Li arrives at the other electrode, and therefore before a short circuit occurs.